Looking glass inhibitors: efficient synthesis and biological evaluation of D-deoxyfuconojirimycin. - Blériot, Y; Gretzke, D; Krülle, T; Butters, T; Dwek, R; Nash, R; Asano, N; Fleet, G (2005)
1,6-Dideoxygalactostatin, the mirror image of 1-deoxy-L-fuconojirimycin, was efficiently prepared from 2,3-O-isopropylidene-L-lyxonolactone in four steps and evaluated as a glycosidase inhibitor.